Analysis of Factors Affecting Brain Metastasis in Limited-Stage Small-Cell Lung Cancer Treated With Definitive Thoracic Irradiation - Wu, Shuting; Wang, Jiezhong; Zhang, Wei; Li, Jiancheng; Wu, Haishan; Huang, Zhiyu; Zhou, Guangrun; Pan, Jianji; Chen, Mingqiu (Frontiers in Oncology, 2020)
Small-cell lung cancer (SCLC) is the most lethal cancer. With the development of chemotherapy and radiotherapy, brain metastasis (BM) emerged as one most predominant treatment failure. However, the factors affecting BM have not been identified completely. The purpose of this study was to investigate the risk factors involved in the development of BM in patients with limited-stage small-cell lung cancer (LS-SCLC) following definitive thoracic radiotherapy (TRT) and to provide a reference for the planning of a clinical treatment strategy. This article shows Poor short-term response to TRT and huger Dmax-T were risk factors for BM. AC following TRT improved patient survival, but not decreased BM. However, due to the limitations associated with the retrospective design of the present study, further prospective clinical trials are required to confirm these conclusions.